Editor FYP report : boys don’t dance - Toh, Beaunice Jun Ying (2017)
‘Boys Don’t Dance’ is a narrative short film following a queer boy named Ono on his journey to being comfortable for who he is. Ono aspires to become a ballet dancer but it is discriminated upon in this conformist society. There is a hidden love affair between Ono and the school’s athlete, Ryan and the latter does not wish to acknowledge this relationship publicly. One day after getting caught in a fling with Ryan, Ono was beaten up by Ryan’s teammates. He begins to question his identity and love for dancing and Ryan. Shortly after, Ono falls into a whimsical world of freaks and meets a group of circus performers who encourage him to be himself.